Effect of Direct Fire Exposure on the Physical and Mechanical Properties of Autoclaved Aerated Concrete (AAC) Based on Ceramic and Gypsum Waste (CGW) as Partial Substitution for Sand - Efil Yusrianto,; Marsi, Noraini; Abdul Manaf, Izzati; Hakim Shariff, Hafizuddin (International Journal of Integrated Engineering, 2024)
Six types of autoclaved aerated concrete (AAC) based on ceramic- gypsum waste (CGW) as partial substitution for sand has been prepared. The compressive strength ranges from 1.64 MPa to 2.13 MPa and work density ranges from 594 kg/m3 to 605 kg/m3. All AAC samples have exposed to direct fire at temperature 923.8 °C for 300 s. The maximum temperatures surface (T1) and opposite surface (T2) were 930.1 °C and 31.7 °C respectively. The average T1 of sample was around of 169.88 °C and average thermal storage around 10.36 % after natural cooling for 900 s. Meanwhile, the average T2 was around 31.3 °C and almost similar with workshops temperature. Except for pure AAC, the samples were showed not crack, burnt and melt during exposed to direct fire testing at temperature 920 °C for 300 s. The direct fire testing has also positive effect on the work density and compressive strength of AAC-CGW. The average work density decreased by around 10.69 % and compressive strength increased by around 12.39 %. The maximum work density was reduced around 14.57 % for AAC-1 and compressive strength was increased around 39.15 % for pure AAC. This work showed that the AAC-1 to AAC-5 are suitable for wall application such as thermal wall especially for fire resistance wall due to its good durability and strength after exposed to direct fire.